Virus Elimination by Direct-Acting Antiviral Agents Impacts Glucose Homeostasis in Chronic Hepatitis C Patients - Cheng, Chun-Han; Chu, Chia-Ying; Chen, Huan-Lin; Lin, I-Tsung; Wu, Chia-Hsien; Lee, Yuan-Kai; Bair, Ming-Jong (Frontiers in Endocrinology, 2022)
Background and Aims: Chronic hepatitis C virus (HCV) infection is associated with dysregulation of glucose homeostasis, including insulin resistance (IR) and type 2 diabetes. However, independent risk factors associated with IR in chronic HCV-infected patients have not been detailly elucidated. Previous data regarding the impact of HCV elimination by direct-acting antiviral agents (DAAs) on glucose homeostasis is insufficient and controversial. This study aimed to analyze the independent factors associated with IR and to evaluate the changes in glucose homeostasis in chronic HCV-infected patients treated with DAAs therapies. Methods: We screened 704 patients with chronic HCV infection who underwent treatment with interferon-free DAAs. Patients’ baseline characteristics, biochemical and virological data were collected. The outcome measurements were their IR and β-cell function assessed by the homeostasis model assessment (HOMA) method at baseline and 12-weeks post-treatment. Results: High IR (HOMA-IR ≥ 2.5) was observed in 35.1% of the patients. Multivariable logistic regression analysis revealed that body mass index (BMI) >25 kg/m2, treatment experience, elevated baseline levels of alanine aminotransferase (ALT) and triglyceride, as well as Fibrosis-4 score >3.25 were independently associated with high IR. In patients who achieved sustained virological response (SVR), no significant change in mean HOMA-IR was observed from baseline to 12-weeks post-treatment (2.74 ± 2.78 to 2.54 ± 2.20, p = 0.128). We observed a significant improvement in β-cell secretion stress from 121.0 ± 110.1 to 107.6 ± 93.0 (p = 0.015). Subgroup analysis revealed that SVR was associated with a significant reduction in mean HOMA-IR in patients with baseline HOMA-IR ≥ 2.5 (5.31 ± 3.39 to 3.68 ± 2.57, p < 0.001), HCV genotype 1 (3.05 ± 3.11 to 2.62 ± 2.05, p = 0.027), and treatment experience (4.00 ± 3.37 to 3.01 ± 2.49, p = 0.039). Conclusions: There were several independent factors associated with IR in patients with chronic HCV infection, including obesity, treatment experience, high serum ALT and triglyceride levels, as well as advanced hepatic fibrosis. After viral elimination by DAAs, we observed a significant reduction in mean HOMA-IR in patients with baseline high IR, HCV genotype 1, and treatment experience.